Use Armstrong’s axioms to prove the derivation functional dependencies.
Use Armstrong’s axioms to prove the derivation functional dependencies
In each step of the proof, Armstrong’s axiom must be specified.
- Consider a relation R=(A,B,C,D,E, F, G) that satisfies the following four FDs: A→B, A→C, CD→EF, F →G
Using the Armstrong Axioms, find the minimal key for relation R. - Consider a relation R=(L, M, N, O, P, Q) that satisfies the following four FDs: L→ M, N→ LO, LQ→ P.Does NQ→PM hold?
If so, show a formal proof.
in progress
Design and Analysis of Algorithms
1 Answer
Anonymous(s) Post
Login to view answer.